Strategy For Improving Customer Satisfaction Towards Service Quality Perception And Brand Image In The Culinary Industry - Dikki Z. Choesrani; Rahmat Kusnedi; Kezia Elsty; Muhammad Irfan; Lilik Hariyanto; Aan Nurhasanah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The results of the analysis show that the perception of service quality has a positive and significant impact on customer satisfaction. If the quality of service is improved, then customer satisfaction will also increase. Service quality is measured through various dimensions such as reliability, responsiveness, and empathy, all of which contribute to the overall evaluation of the customer experience. The brand image also plays an important role in shaping customer satisfaction. Research found that brand image has a positive influence on customer satisfaction, although its impact is smaller compared to service quality. A positive brand image can enhance customers' perception of the quality of service provided. Research shows that the total impact of service quality on customer satisfaction is around 42.78%, while brand image contributes approximately 15.13%. In other words, service quality has a greater impact compared to the brand image in enhancing customer satisfaction. From this analysis, it can be concluded that to improve customer satisfaction in culinary industrys, it is important to focus on enhancing service quality. This includes improvements in service responsiveness and reliability, as well as building a positive brand image. This, culinary industry can be more effective in meeting student expectations and increasing their satisfaction levels.   Keywords: Service Quality, Brand Image, Customer Satisfaction, Customer Loyalty